Implementasi Geocrime Berbasis Android - Joko Santoso (Media Aplikom, 2017)
: According to the National Statistics Agency, During the period 2008 - 2014, the type of crime in theft is a crime that most occur in the village in Indonesia. Android-based smartphone is one tool that can be used to report the crime. This study aims to analyze, design and build an Android-based system that can be used by users to share information about the locations of the occurrence of a crime, so as to increase awareness of users to the locations he visited. Data is collected using the method of observation. System is developed using three of the seven stages there are in the system life cycle proposed by Kusrini. System is tested using alpha and beta testing. The result of alpha testing shows that there is no processing errors and functionally release the results as expected. Beta testing results indicate that these applications can provide convenience for users to see and report crimes that occur around them. Keywords: Crime, Android, GPS, Geocoding